Ecologia comparativa das espécies do gênero Vanzosaura (Squamata: Gymnophthalmidae) da Caatinga e do Cerrado. - Lima, Ana Maria Cristina Malta Araujo (2014)
Populations of species with a wide geographical distribution can be subjected of a broad range of environmental conditions, exposed to different selective pressures, which in association with time of isolation and genetic variability may induce to different adaptive responses (phenotypic plasticity). The genus Vanzosaura belongs to Gymnophthalmidae family having a diagonal distribution in dry areas of South America, occurring in at least three separate formations (Cerrado, Caatinga and Chaco). Herein, we compared data on reproduction, diet and morphology of individuals of the species Vanzosaura multiscuta, sampled in areas of Caatinga and V. rubricauda and V. savanicola from Cerrado. The diet of the species showed no significant differences, composed of spiders, orthoptera and plecoptera, the most consumed categories. Clutch size was the same for all species (02 eggs) what appears to be a synapomorphy in gymnophthalmids. Vanzosaura multiscutata showed continuous reproduction throughout the year with evidence of sequential litters and smaller eggs. Vanzosaura savanicola and V. rubricauda, had concentrated breeding in the dry season and early wet season with larger eggs. The species present morphometric differences, in which the Cerrado species showed greater length and snout vent lenght, wider body and shorter tail compared with the specie of the Caatinga. Both the phylogeny and the ecology influence the life history of Vanzosaura spp. The diet is more influenced by historical factors, and the morphology and reproduction by ecological factors.